A Theory of the Attenuator-Coated Helical Slow-Wave Structure of a Traveling-Wave Tube - Jain P.K.; Basu B.N. (My University, 2025)
A theory of the attenuator-coated helical slow-wave structure of a traveling-wave tube has been developed by considering the helix turns to be effectively shorted by a resistive coating. The transcendental dispersion relation is solved for the complex propagation constant that appears in the argument of the modified Bessel functions occurring in the dispersion relation of the structure. Power propagating down the structure is interpreted for the interaction impedance in the presence of the attenuator-coating losses. The dependence of the attenuation and phase propagation constants as well as the interaction impedance on the surface resistivity of the coating, the operating frequency, the thickness/proximity of the envelope, the permittivity of the dielectric, and the pitch of the helix have been studied for two situations in which the attenuator coating is applied 1) inside a dielectric tube that the helix fits into, the whole enclosed in a metal envelope, and 2) over a dielectric tube enclosure for the helix. The analysis gives one a method to find the optimum surface resistivity for the desired attenuation and interaction impedance as well as an understanding of the role of the attenuator coating on the dispersion of the structure and the gain-frequency response of the device. © 1988 IEEE